L’assurance et le sida - Dumais, Christian N. (Assurances, 1991)
Statistics, new norms in the insurance industry and insurance conditions are the three subjects of this article which provides the general background of the impact of AIDS on insurance. According to the author, insurers must and can adjust to the problem that this terminal disease presents by increasing their premiums and tightening their underwriting policies.